Isolation and Identification of Some Probiotic Bacteria and Their Potential Role in Improving Immune Response and Resistance of Nile Tilapia (Oreochromis niloticus) in Comparison with a Commercial Product - Mosleh M. Abomughaid (International Journal of Microbiology)
This work aimed to retrieve a field isolate of probiotic from Nile tilapia (Oreochromis niloticus) and compare the obtained results with a commercial probiotic product through experimental studies. The study was conducted on 250 Nile tilapia. Ten fish were used to isolate the probiotic strain. Two isolates showed an in vitro inhibitory effect against pathogenic A. hydrophila. The isolate with the largest zone was identified by PCR. Sixty fish were used to test the safety of a potential probiotic. One hundred and eighty fish were used in a two-month feeding experiment. Fish were divided into 3 groups, group (1): the control, group (2): fed on potential probiotics, and group (3): fed on commercial probiotic (Organic Green™). The effects of tested products on the immune response were recorded in all groups. After one and two months of feeding experiment, blood and nonspecific immune parameters were evaluated. Disease resistance against Aeromonas hydrophila was evaluated through challenge experiment. The histopathology of the treated groups was fully recorded in comparison with the control group. The potential probiotic based on the in vitro antimicrobial activity test was identified as P. putida using routine and gel electrophoresis and 16S rRNA sequencing. During the first and the second month of experiment, there was a highly significant increase in the survival percent of the experimental fish in both treated groups with probiotics. In the first phase of the experiment, a significant increase in the haematocrit values and NBT, lysozyme activity, and phagocytic activity was seen in all treated groups in comparison with the control. The increase in the TLC was significant in the group fed with P. putida in comparison with the control group. In the second phase, a nonsignificant increase in the hematocrit values and significant increases in the NBT and phagocytic index were seen in P. putida and organic green groups in comparison with the control group. The TLC and DLC revealed nonsignificant changes in the treated groups in comparison with the control. The RLP in the groups treated with P. putida was higher than that in those treated with organic green. Although probiotics are an important management tool in aquaculture, it should be subjected to scientific laboratory tests and field measurements.